Kontrak Validitas dalam Muamalat (Kajian Literatur) - Rahmad Bahagia; Sri Sudiarti (CERED Indonesia Institute, 2023)
This research is a library research where the data comes from library sources, namely literature review through library research. The literature study is closely related to theoretical studies and other references related to the relevance of the Al-Qur'an, Hadith and other sources of Islamic law in the perspective of sharia economics. In the muamalah rules, everything is permissible unless there is an argument against it. Basically, there are three things that result in a transaction being prohibited, namely because: the substance is haram (haram Li dzatihi), haram other than the substance (haram Ii ghairihir aridhiy, and haram because the contract is not valid. Economic practices that are against pleasure, the presence of elements of qimar and maisir , gharar and usury are economic activities that are prohibited in Islam. The ultimate goal of economic practice is to realize maqashid ash-shariah as a parameter of the legality of economic transaction contracts. Trading on the stock exchange is one example of economic practice that is not in accordance with maqashid ash-shariah so it is necessary modifications are made with the aim of maintaining economic viability.